2003
DOI: 10.1152/ajprenal.00251.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human organic cation transporter hOCT2 by PKA, PI3K, and calmodulin-dependent kinases

Abstract: Properties and regulation of the human organic cation (OC) transporter type 2 (hOCT2) expressed in HEK-293 cells were extensively characterized using the fluorescent OC 4-[4-(dimethylamino)styryl]- N-methylpyridinium (ASP+). ASP+ uptake was electrogenic and inhibited by TPA+ (EC50 = 2.7 μM), tetraethylammonium (EC50 = 35 μM), cimetidine (EC50 = 36 μM), or quinine (EC50 = 6.7 μM). Stimulation with carbachol or ATP decreased initial uptake by 44 ± 3 ( n = 14) and 34 ± 4% ( n = 21), respectively, independently of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
96
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 44 publications
7
96
2
Order By: Relevance
“…Regulation of OCTN2 by phosphorylation/dephosphorylation mechanisms was expected due to previous reports regarding such effects on OCT1, OCT2, and OCT3 [5][6][7] and the presence of putative phosphorylation sites on the OCTN2 protein (see Figure 1). Nevertheless, the results gathered while testing this hypothesis suggest that the contributions of phosphorylation in the regulation of OCTN2 are minimal in this model of the placental barrier.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Regulation of OCTN2 by phosphorylation/dephosphorylation mechanisms was expected due to previous reports regarding such effects on OCT1, OCT2, and OCT3 [5][6][7] and the presence of putative phosphorylation sites on the OCTN2 protein (see Figure 1). Nevertheless, the results gathered while testing this hypothesis suggest that the contributions of phosphorylation in the regulation of OCTN2 are minimal in this model of the placental barrier.…”
Section: Discussionmentioning
confidence: 55%
“…Ciarimboli et al report that OCT1 activity decreased upon protein kinase A (PKA) activation and upon inhibition of calmodulin, calmodulin-dependent kinase II, and p56 lck tyrosine kinase [5]. This same group also determined that OCT2 uptake is inhibited by phosphatidylinositol 3-kinase (PI3K) and PKA and activated by calmodulin-dependent signaling [6]. OCT3 regulation by phosphorylation/dephosphorylation mechanisms was investigated by Martel et al, who observed reduced MPP + uptake in the presence of Ca 2+ /calmodulin pathway inhibitors, phosphodiesterase inhibitors, and an alkaline phosphatase (ALP) inhibitor [7].…”
Section: Introductionmentioning
confidence: 98%
“…This can explain why different isoforms are differently regulated. hOCT1 (11), hOCT2 (10), and hOCT3 (12), for example, are not activated by PKC stimulation, but by various other regulatory pathways such as PKA or Ca 2ϩ -calmodulin (10,12). In this study, we attempted to determine which of the described five putative PKC sites (23) is responsible for PKC-mediated regulation of rOCT1 and whether transporter phosphorylation changes substrate affinities.…”
Section: Discussionmentioning
confidence: 99%
“…PKC has been shown to directly phosphorylate rOCT1, leading to a conformational change at the substrate binding site (8): PKCmediated phosphorylation increased the apparent affinities of rOCT1 for various substrates. However, in HEK293 cells stably expressing the hOCT2, PKC seemed not to stimulate the transporter, whereas its activity was reduced by PI3K and PKA activation and was stimulated by an endogenously active calmodulin-dependent signaling pathway (10). Similar results have been obtained with HEK293 cells stably expressing hOCT1 (11) or the human extraneuronal monoamine transporter (or hOCT3) (12), which were not affected by PKC activation but again were inhibited by PKA and stimulated by an endogenously active calmodulin-dependent signaling path-way.…”
mentioning
confidence: 94%
“…13,14 Post-transcriptional regulation of OCT-1 by phosphorylation status 15 and such compounds as protein kinase A (PKA), Src-like p56, and CaM also have been demonstrated. [16][17][18] Both quantitative and qualitative changes in OCT-1 may have an impact on imatinib uptake. We hypothesized that a functional assay of imatinib uptake into patient cells may provide the most clinically predictive assay of OCT-1 function.…”
Section: Introductionmentioning
confidence: 99%